3D numerical modeling of the deformation and failure mechanisms of batter pile groups subjected to fault ruptures - Mukhtiar Ali Soomro; ZiQing Zhu; Muhammad Shamrooz Aslam; Hazrat Bilal; Abid Yahya; Irfan Anjum Badruddin (Scientific Reports)
Abstract Fault ruptures induced by earthquakes pose a significant threat to constructions, particularly underground structures such as pile foundations. Among various foundation types, batter pile foundations are widely used due to their ability to resist inclined forces. To gain new insights into the response of batter pile groups to fault ruptures caused by earthquakes, this study investigates the deformation and failure mechanisms of batter pile groups due to the propagation of normal and reverse fault ruptures using 3D numerical modeling. An advanced hypoplastic constitutive model for clay, which accounts for small-strain stiffness, and a concrete damage plasticity (CDP) model are employed to simulate the soil and the batter pile foundation, respectively. Results show that following fault propagation, nearly 10% tilting and significant displacement occurred at the pile cap, indicating a total failure of the batter pile foundation. It was also observed that the piles bent towards the slipping direction of the hanging wall. Tensile damage to the pile foundation was notably more severe than compression damage. The most severely damaged regions were not only located at the joints between the piles and the pile caps but were also found along the pile shafts.